A Surface Roughness Analysis of 3D Printed Mold Inserts Using ABS-Like and TR300 Resins: An Evaluation of Printing Angles and Material Performance for Injection Molding Applications - Weeradeachlikul, Soontorn; Chuanasa, Jak (Engineering, Technology & Applied Science Research, 2025)
This research focuses on a comparative study of the surface roughness of parts fabricated using Stereolithography (SLA) 3D printing technology. The objective is to compare the surface roughness of printed parts at various build angles, ranging from 0° to 90°, using two types of resins: Acrylonitrile Butadiene Styrene (ABS)-like resin and TR300 resin. The study aims to determine whether the surface roughness trends are consistent between the two materials and to analyze the effect of printing angle on surface quality. This analysis will identify the optimal printing conditions for producing high-quality insert mold cavities used in plastic injection molding. The experimental results reveal that TR300 resin consistently provides a smoother surface finish than ABS-like resin across all printing angles. The lowest surface roughness was observed at a 0° printing angle with TR300 resin, showing values of Ra = 0.175 µm, Rz = 1.123 µm, and Rt = 1.136 µm. In comparison, the lowest surface roughness for ABS-like resin at the same angle was Ra = 0.256 µm, Rz = 1.690 µm, and Rt = 2.170 µm. These findings indicate that the most suitable condition for producing insert mold cavities for high-quality plastic injection molds is using TR300 resin printed at a 0° angle. This is due to the fact that the resulting surface roughness falls within the recommended range for mold cavities (Ra = 0.2–1.6 µm), making it ideal for precision applications in injection molding.